2015
DOI: 10.1111/jan.12630
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the reasons why Chinese older people do not wish to tell their life stories

Abstract: An understanding about the tension existing in cultural/generational narratives of the older people may help health professionals to provide them with a supportive environment for their continuous construction of social identities. This may contribute to their better social health. Equally important is to provide an opportunity for them to share their stories and engage in family and cross-generational dialogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In addition, older women have a higher risk of loneliness than older men, and women readily share their negative emotions compared with men (50). Women can easily release old resentment by communicating with their peers with similar symptoms or experiences, ultimately improving their social and emotional well-being (51). Studies with larger clinical sample sizes and subjects with diverse severity and symptom manifestations should be conducted to further validate the effectiveness of the TD-GCBT approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older women have a higher risk of loneliness than older men, and women readily share their negative emotions compared with men (50). Women can easily release old resentment by communicating with their peers with similar symptoms or experiences, ultimately improving their social and emotional well-being (51). Studies with larger clinical sample sizes and subjects with diverse severity and symptom manifestations should be conducted to further validate the effectiveness of the TD-GCBT approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although no statistically significant difference was observed over time between the groups, the qualitative part of this study revealed that our participants found the LSB to be meaningful to them. Some stated that they would be able to let their offspring and others know more about them from their life storybooks (Chan & Lai, ). Studies to explore the participants’ views of the benefits or adverse outcomes of LSW would shed light on the ways in which LSW can or cannot be useful.…”
Section: Discussionmentioning
confidence: 99%